Space temperature policy towards net-zero: recommendations from a systematic review of UK HEI heating policies. Issue 2 (17th February 2023) - New, Kathy; Tyler, Adam; Friday, Adrian; Hazas, Mike; Gormally, Alexandra
ABSTRACT: The UK government has committed to reducing its carbon emissions to net-zero by 2050. Higher education institutions (HEIs) are high energy users, with the largest proportion of their energy demand for space heating; an area still dominated by carbon-intensive fuels. This research addresses the UK HEI space temperature policy landscape, making direct links between space temperature policy and carbon management, advocating the development of evidence-based policies as a critical tool for reducing carbon emissions within the sector. Sixty-six space temperature policies were reviewed, and five experienced energy managers were interviewed to understand the range, development and use of space temperature policies in UK HEIs. The research identified a lack of consistency across these policies, leading to missed opportunities for making energy and carbon savings. The research highlights gaps in the available data and literature needed to connect policy to its effectiveness, and identifies the use of policy as a defensive tool against complaints rather than an active driver of energy reduction. A series of recommendations are proposed for national and institutional policymakers, suggesting areas for improvement and future research to facilitate effective development and practice in space temperature policy towards net-zero .